Current Sensitivity Pattern of Salmonella Species in Children Presenting at a Tertiary Care Hospital - Muhammad Rafique, Sharmeen Nasir, Amber Kamran, Waseem Jamalvi, Ammarah Jamal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Enteric fever is a common and treatable pediatric bacterial infection, but emerging drug resistance has been a real challenge for treating physicians. Since 2016, Pakistan is facing the epidemic of Extensively drug resistant (XDR) salmonella typhi. Objective: To determine the clinical presentation and current pattern of sensitivity of salmonella species in children diagnosed with enteric fever. Study Design: Descriptive, Cross sectional Place and Duration of Study: Pediatric department of Dr. Ruth K. M. Pfau Civil Hospital Karachi, from July to December 2022. Methods: Medical records of patients 1 month to 12 years of age, diagnosed as enteric fever on positive blood culture for salmonella, were inducted into the study by non-probability convenient sampling. The clinical manifestations of patients and sensitivity and resistance patterns of salmonella were recorded. Data was analyzed using SPSS version 22. Results: A total of 140 children had enteric fever, out of which 60.7% were male. Mean age of the patients was 4.48+2.47 years. Most common symptom was fever in 140 (100%), followed by anorexia in 97 (69.2%) and abdominal pain in 70 (50%). Blood culture reports showed Extensive drug resistance in 105 (75%), Multi drug resistance in 3 (2.14%) and Non-resistance in 7 (5%). Salmonella Typhi isolates were sensitive to Carbapenems in 140 (100%), Azithromycin 139 (99.2%) and Piperacillin/Tazobactam in 60 (42.8%). Conclusion: XDR enteric fever is still the most common resistance pattern identified in admitted patients with enteric fever. Large scale public health measures and antibiotic stewardship are required to fight this disease. Keywords: Typhoid fever, Salmonella Typhi, Drug resistance, Infection, Epidemic